Mass spectrometry of the white adipose metabolome in a hibernating mammal reveals seasonal changes in alternate fuels and carnitine derivatives - Heinis, Frazer I.; Alvarez, Sophie; Andrews, Matthew T. (Frontiers in Physiology, 2023)
Mammalian hibernators undergo substantial changes in metabolic function throughout the seasonal hibernation cycle. We report here the polar metabolomic profile of white adipose tissue isolated from active and hibernating thirteen-lined ground squirrels (Ictidomys tridecemlineatus). Polar compounds in white adipose tissue were extracted from five groups representing different timepoints throughout the seasonal activity-torpor cycle and analyzed using hydrophilic interaction liquid chromatography-mass spectrometry in both the positive and negative ion modes. A total of 224 compounds out of 660 features detected after curation were annotated. Unsupervised clustering using principal component analysis revealed discrete clusters representing the different seasonal timepoints throughout hibernation. One-way analysis of variance and feature intensity heatmaps revealed metabolites that varied in abundance between active and torpid timepoints. Pathway analysis compared against the KEGG database demonstrated enrichment of amino acid metabolism, purine metabolism, glycerophospholipid metabolism, and coenzyme A biosynthetic pathways among our identified compounds. Numerous carnitine derivatives and a ketone that serves as an alternate fuel source, beta-hydroxybutyrate (BHB), were among molecules found to be elevated during torpor. Elevated levels of the BHB-carnitine conjugate during torpor suggests the synthesis of BHB in white adipose mitochondria, which may contribute directly to elevated levels of circulating BHB during hibernation.